Nasotracheal intubation in pediatrics: a narrative review - Kim, Jieun; Jeon, Sooyoung (Journal of Dental Anesthesia and Pain Medicine, 2024)
Nasotracheal intubation (NTI) plays an important role in pediatric airway management, offering advantages in specific situations, such as oral and maxillofacial surgery and situations requiring stable tube positioning. However, compared to adults, NTI in children presents unique challenges owing to anatomical differences and limited space. This limited space, in combination with a large tongue and short mandible, along with large tonsils and adenoids, can complicate intubation. Owing to the short tracheal length in pediatric patients, it is crucial to place the tube at the correct depth to prevent it from being displaced due to neck movements, and causing injury to the glottis. The equipment used for NTI includes different tube types, direct laryngoscopy vs. video laryngoscopy, and fiberoptic bronchoscopy. Considering pediatric anatomy, the advantages of video laryngoscopy have been questioned. Studies comparing different techniques have provided insights into their efficacy. Determining the appropriate size and depth of nasotracheal tubes for pediatric patients remains a challenge. Various formulas based on age, weight, and height have been explored, including the recommendation of depth-mark-based NTI. This review provides a comprehensive overview of NTI in pediatric patients, including the relevant anatomy, equipment, clinical judgment, and possible complications.